Regional Gas Interconnectivity And The Implications Of Trade In Liquified Natural Gas For Energy Security Of Non-Eu Western Balkan States - Dirioz, Ali Oguz; Erbil, Eray (Journal of Sustainable Development Law and Policy, 2025)
The article examines the state of energy security in the Balkans, the level of regional gas interconnectivity and the role of trade in liquefied natural gas (LNG) in enhancing energy security in the region. The study shows that infrastructure investments are required in the Balkans. However, the small size of the Balkan market lowers investment incentives. In this context, the policy entrepreneurship of the EU Commission can increase solidarity and investments in the Balkans. Moreover, planned and existing pipeline-LNG projects in the periphery of the Balkans can enhance the energy security of these countries.